University Students Attitudes Towards Digital Media News Coverage of Corruption Issues and its Effects in Saudi Arabia - Al-Qahtani, Saud Rubaya Mousa (Journal of Humanities & Social Sciences, 2022)
Is "digitization" considered as an alternative tool of information, production of investigative reports, supporting anti-corruption, electronic participation, and affecting the audiences? To find out, the study explores attitudes towards digital media coverage of corruption issues and their effects, involved with 800 of Saudi university students by an electronic questionnaire. The findings show that traditional media is a primary news source, freedom of expression is low, coverage is characterized by far away from journalistic ethics and weak professional, and it affected a more negative way. The attitudes are correlated with the behavior towards corruption, and the effective role of digital media in anti-corruption is related to causes of its; which means the importance of developing corruption content and placing them within agenda. We argue through frame "silent Attitudes," that consumption and impact of information come in accordance with social determinism, away from digital media.
Keywords: trends; news coverage; digital media; corruption; repercussions; freedom of expression